2009
DOI: 10.1139/x09-043
|View full text |Cite
|
Sign up to set email alerts
|

Soil greenhouse gas and nutrient dynamics in fertilized western Canadian plantation forests

Abstract: We explored the impacts of fertilization on soil greenhouse gas fluxes and underlying soil nutrient transformations using short-term (up to 7 months) simulated operational fertilization with urea-nitrogen or nitrogen, phosphorus, potassium, and micronutrients in lodgepole pine ( Pinus contorta Dougl. ex Loud. var. latifolia Engelm.), western hemlock ( Tsuga heterophylla (Raf.) Sarge.), and Douglas-fir ( Pseudotsuga menziesii (Mirb.) Franco) forests in British Columbia. Urea appeared to be rapidly mineralized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 47 publications
2
13
0
2
Order By: Relevance
“…In the boreal forest, N deposition significantly inhibited CH 4 uptake, and the inhibitory effects increased with increasing N treatment levels. These results were consistent with previous findings reporting the inhibition of CH 4 uptake in N-fertilized forest soils [16,44,45]. These authors reported a Meta-analysis revealing that soil CH 4 uptake was significantly reduced 38% across all ecosystems under N application.…”
Section: Effects Of N Addition On the Soil Ch 4 Uptakesupporting
confidence: 92%
“…In the boreal forest, N deposition significantly inhibited CH 4 uptake, and the inhibitory effects increased with increasing N treatment levels. These results were consistent with previous findings reporting the inhibition of CH 4 uptake in N-fertilized forest soils [16,44,45]. These authors reported a Meta-analysis revealing that soil CH 4 uptake was significantly reduced 38% across all ecosystems under N application.…”
Section: Effects Of N Addition On the Soil Ch 4 Uptakesupporting
confidence: 92%
“…This is generally consistent with prior soil measurements and high N deposition in the Haliburton Highlands region (Gradowski and Thomas 2008). Relative to other forests with coarse-textured soils elsewhere in Ontario and Canada, soils in our study had slightly higher mean rates of in situ N 2 O emissions (Basiliko et al 2009, Peichl et al 2009). However contrary to our initial predictions, mean in situ N 2 O efflux rates were still low, occasionally negative, and on any given sampling date were not significantly greater than zero (Table 1C; Figure 1).…”
Section: Introductionsupporting
confidence: 92%
“…Basiliko et al 2009), and liming and P+K fertilization decreased in situ oxidation rates (Table 1C; Figure 1), an unexpected pattern that is discussed below. While controls exhibited the highest level of in situ soil respiration and P+K and P+K+L the lowest, there were no significant average seasonal differences observed (Table 1C; Figure 1).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Other authors suggest that salts have an inhibitory effort on methanotrophic bacteria due to osmotic stress [29]. Most studies have reported an inhibition of CH 4 uptake in response to N input in forest soils [30][31], although inverse effects have also been reported. The fact that N deposition inhibits CH 4 uptake implies that boreal forests may remove less CH 4 under future increased N deposition conditions in China.…”
Section: Effect Of N Deposition On Soil Ch 4 Uptakementioning
confidence: 99%